2023
DOI: 10.3389/fimmu.2023.1179014
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus brevis alleviates the progress of hepatocellular carcinoma and type 2 diabetes in mice model via interplay of gut microflora, bile acid and NOTCH 1 signaling

Abstract: Type 2 diabetes (T2DM) clinically exhibits a higher incidence of hepatocellular carcinoma (HCC), contributing to a lousy prognosis in patients harboring both diseases. Microflora-based therapy draws attention with low side effects. Accumulating evidence shows that Lactobacillus brevis can improve blood glucose and body weight of the T2DM mice model and reduce several cancer incidences. However, the therapeutic effect of Lactobacillus brevis in affecting the prognosis of T2DM+HCC remains unknown. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Lactobacillus , a probiotic, has been confirmed to have the function of improving the intestinal mucosal barrier, reducing inflammation and maintaining the balance of blood sugar. 66 The result showed that the relative abundance of Lactobacillus in T2DM mice was decreased. However, it could be regulated by ingesting RRS, and the abundance gradually increases with an increase in the RRS dose.…”
Section: Resultsmentioning
confidence: 97%
“…Lactobacillus , a probiotic, has been confirmed to have the function of improving the intestinal mucosal barrier, reducing inflammation and maintaining the balance of blood sugar. 66 The result showed that the relative abundance of Lactobacillus in T2DM mice was decreased. However, it could be regulated by ingesting RRS, and the abundance gradually increases with an increase in the RRS dose.…”
Section: Resultsmentioning
confidence: 97%
“…It would be interesting to recommend a larger study with simultaneous measurements of HbA1c, succinate and other serum parameters to confirm this observation. This may open up prospects for using specific succinate consuming bacteria that are beneficial to host health or to administer succinate-consuming probiotics and promote their growth through high fibre dietary intervention, which is expected to lead to the uptake of excessive succinate and provide new avenues for treating related diseases ( Muhammad et al, 2023 ; Sharma, Bhardwaj & Singh, 2016 ; Bernier et al, 2021 ; Chen et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…The observation of this study also indicates the potential of Bifidobacterium angulatum in amelioration of hyperglycaemia and reduction of HbA1c levels. On the other hand, Levilactobacillus brevis has been previously reported to alleviate the progression of type 2 diabetes in animal models, via interplay of gut microflora, bile acid and NOTCH 1 signalling 72 . Also, Levilactobacillus brevis possess inhibitory effects on α-amylase and α-glucosidase activities, and has been reported to have anti-diabetic properties 73 .…”
Section: Methodsmentioning
confidence: 99%